Sight unseen : gender and race through blind eyes - Kaschak, Ellyn, 1943- (Columbia University Press, 2015)
'Sight Unseen' reveals the cultural and biological realities of race, gender, and sexual orientation from the perspective of the blind. Through ten case studies and dozens of interviews, Ellyn Kaschak taps directly into the phenomenology of race, gender, and sexual orientation among blind individuals, along with the everyday epistemology of vision. Her work reveals not only how the blind create systems of meaning out of cultural norms but also how cultural norms inform our conscious and unconscious interactions with others regardless of our physical ability to see.